Development Of A Three-Jaw Gripper For Rhino Robot For Part Location - Shirlyn , Lojumin (UTeM, 2008)
This Bachelor Degree Project is about development of a three-jaw gripper for Rhino robot for part location. There are many advantages of robot in pick and place in industrial. They can do dangerous work, repetitive operation and extreme temperature. The developed gripper was a three-jaw gripper design. The gripper is made from wood. The developed gripper will be mounted to the robot arm for a pick and place operation. The developed gripper can grasp three types of object which are sphere, cylinder and cube. The signal produce from the robot will detect any missing parts from the conveyor placed opposite the loading system. When the signal received, the gripper will take the missing part from the storage system and locate them at the conveyor. Many considerations have been taken to accomplish the objectives. The design of the finger gripper is considering the weight, size and the appearance of the three types of object which are cube, cylinder and sphere. The finger gripper developed is proven that can grasp the three types of object which are cube, cylinder and sphere.